A Controvérsia Em Torno Do Projeto De Lei 122/2006: Uma Análise Da Oposição De Parlamentares Evangélicos À Criminalização Da Homofobia. - Bortolin, Paula Andrea Gomes [UNIFESP] (2018)
Bill (Proposition Of Law) Number 122/2006 (Kown In Brazil As "Projeto De Lei 122/2006"), Was Proposed Aiming To Outlaw Prejudice And Discrimination Based On Sexual Orientation. It Suffered Strong Opposition From Evangelical Parliamentarians. Those Agents Opposing The Bill Organized Themselves To Curb It Into Going To Voting. A Series Of Justifications Were Used To Oppose The Outlawing Of Homophobia In The Media, Seeking To Bring Together Strength And Legitimacy To Its Arguments And Positions. The Main Goal Of This Research Is To Map Such Controversy, Focusing The Group Opposing The Bill. This Analysis Pretends To Uncover The Grammar, The Categories, And The General Principles Used In The Speeches And Writings Of The Evangelical Actors (Individual Or Collectives), Looking Out To Understand Which Elements Were Mobilized To Thicken Generality And Reliability To These Perspectives.